Wprowadzanie controllingu do małych i średnich przedsiębiorstw jako przejaw myślenia strategicznego - Nowosielski, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the article necessity of controlling usage in small and medium enterprises was motivated, reading the act of implementing this conception as indication of strategic thinking of the owner. General (framework) technique of controlling implementing in such enterprises was shown. The main steps of this technique were characterized. Problems, which appears during realization of these steps were also discoursed. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 302-309